Steering Mast Cells or Their Mediators as a Prospective Novel Therapeutic Approach for the Treatment of Hematological Malignancies - Mehtani, Deeksha; Puri, Niti (Frontiers in Oncology, 2021)
Tumor cells require signaling and close interaction with their microenvironment for their survival and proliferation. In the recent years, Mast cells have earned a greater importance for their presence and role in cancers. It is known that Mast cells are attracted towards tumor microenvironment by secreted soluble chemotactic factors. Mast cells seem to exert a pro tumorigenic role in hematological malignancies with a few exceptions where they showed anti-cancerous role. This dual role of mast cells in tumor growth and survival may be dependent on the intrinsic characteristics of the particular tumor, differences in tumor microenvironment according to tumor type, and their interactions and heterogeneity of mediators released by mast cells in the tumor microenvironment. In many studies, Mast cells and their mediators have been shown to affect tumor survival and growth, prognosis, inflammation, tumor vascularization and angiogenesis. Modulating mast cell accumulation, viability, activity and mediator release patterns may thus be important to in controlling these malignancies. In this review, we emphasize on the role of mast cells in lymphoid malignancies and discuss strategies for targeting and steering mast cells or their mediators as a potential therapeutic approach for the treatment of these malignancies.